2021
DOI: 10.1055/s-0041-1729505
|View full text |Cite
|
Sign up to set email alerts
|

Pedicled Chimeric Perforator Flap Based on Inferior Gluteal Vessel Axis for the Reconstruction of Stage-Four Primary Ischial Pressure Sores—A New Design

Abstract: Background “Subfascial void reconstruction” in ischial pressure sores (IPSs) goes a long way in the amelioration of the common complications like persistent drainage, infection, wound dehiscence, and late recurrence. No locoregional flaps suffice this requirement. So we have designed a chimeric pedicled flap based on the inferior gluteal vessel axis (IGVA) perforators with two tissue components: (1) Pacman-style fasciocutaneous flap on a perforator and (2) gluteus maximus muscle (inferior portion) on another i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…This study confirmed that the chimeric flap could effectively cover the exposed prosthesis and obliterate the dead space. Arikrishnan et al 13 reconstructed ischial pressure sores using a chimeric flap based on an inferior gluteal artery perforator, providing evidence that the gluteal chimeric perforator flap can obliterate subfascial voids. However, no study has reported the use of CPPF based on SGAP to reconstruct complex sacrococcygeal defects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study confirmed that the chimeric flap could effectively cover the exposed prosthesis and obliterate the dead space. Arikrishnan et al 13 reconstructed ischial pressure sores using a chimeric flap based on an inferior gluteal artery perforator, providing evidence that the gluteal chimeric perforator flap can obliterate subfascial voids. However, no study has reported the use of CPPF based on SGAP to reconstruct complex sacrococcygeal defects.…”
Section: Discussionmentioning
confidence: 99%
“…Each part of the flap can have relatively independent anatomical components, ranging from the skin to the muscle, providing the possibility of repairing defects at different locations. In a case series involving 21 patients, Arikrishnan et al 13 confirmed the feasibility of pedicled chimeric perforator flaps in the reconstruction of ischial pressure sores involving dead space.…”
mentioning
confidence: 92%